An Exploratory Analysis of the Chronic Rhinosinusitis Online Support Community - Ruben Ulloa; Benjamin Tam; Francis Reyes Orozco; Carlos X. Castellanos; Michael T. Chang; Kevin Hur (OTO Open, 2023)
Abstract Objective To characterize the users of the largest chronic rhinosinusitis (CRS) online support communities (OSCs), describe the perceived benefits of OSCs for their users, and understand how patient medical decision making is affected by membership in OSCs. Study Design Cross‐sectional online survey. Setting Online. Methods A cross‐sectional online survey was adapted from the existing literature on patient support groups and modified for CRS patients. The survey was posted on multiple Facebook/Reddit groups aimed at providing support toward patients with CRS. Survey data was collected over 3 months and analyzed thereafter. Results There were 127 total participants. The majority were female (65.35%), white (76.98%), and the median age was 38 years. Just under half of patients had nasal polyps (48.67%) and 54.54% had undergone surgery. Many participants (69.42%) reported engaging in the OSC at least multiple times per month. The most common reason for joining an OSC was to learn tips on how to manage CRS (89.7%) and the most achieved goal from membership was hearing from others undergoing a similar experience (79.5%). Involvement in an OSC impacted knowledge of CRS in 87.41% of participants. Most users (81.1%) would recommend membership in an OSC and 54.33% reported the OSC influenced their medical decision‐making. Conclusion A majority of patients with CRS who frequently engage in an OSC for CRS have a positive experience. OSCs are a resource that CRS patients utilize to manage their disease.